IMPACT OF EDUCATIONAL ASPIRATIONS ON VOCATIONAL CHOICES OF THE FEMALE SECONDARY SCHOOL STUDENTS IN ONDO WEST LOCAL GOVERNMENT AREA OF ONDO STATE, NIGERIA - Abiola, Jimoh (European Scientific Journal, ESJ, 2014)
The study investigates the impact of educational aspiration on vocational choices of the female secondary school students in Ondo West Local Government of Ondo State, Nigeria. The study used descriptive survey design targeting some of the female students from the 3 Female Secondary School in Ondo West Local Government. Purposive sampling technique was used to select 3(three) schools, from which 200 students were selected from each schools using simple random sampling. Data was used using questionnaire. Simple percentage and frequency count were used to analyze data obtained. From the analysis of the data collected, it was established that environment has a great effect on the educational aspiration on vocational choices of the female secondary school students. However, the socio-economic status of parent also has an impact on the educational aspiration of vocational choices of the female secondary school students. Based on the findings, the following recommendation were made: since the environment affects the educational aspiration of vocational choices of the female secondary school students, Ondo State should provide some schools that are adequately staffed and equipped with all the facilities that are necessary for upward performance in education. It is hoped that the findings of the study will equip the administrators to know the impact of educational aspiration on vocational choices of female students, in order to benefits the students, parents and the school system.